Propuesta de un plan estratégico para la empresa de Servicios aéreos conexos “Aeroconexos Cía. Ltda.”, en La parroquia Shell, cantón Mera de la provincia de Pastaza para el año 2017 - Vega Orellana, Catherine Gloria (2017)
The present titling project is based on the lack of a strategic plan for the company AEROCONEXOS CÌA. LTDA, for which it has been determined as a general objective Design a Strategic Plan to improve the development and progress of the company AEROCONEXOS CÍA. LTDA., Of the Shell parish, of the canton Mera in the province of Pastaza, also developed specific objectives such as: diagnosis of the current situation of the company, internal and external analysis through the SWOT determining the respective strengths, opportunities, weaknesses and threats , elaborate and interpret the respective matrices EFE, EFI, SWOT AND HIGH IMPACT, which allowed to determine the corporate strategies and finally to make the budget of expenses for the implementation of the plan. The methodology used in the present investigation includes the following methods: scientific, deductive and inductive and among the research techniques are the surveys made to the employees of the company which are 8 people among pilots, dispatcher, mechanics, guard and manager, also to the different clients both fixed and contingent for which 100 surveys were carried out and finally an interview was made to the president of the company, obtaining from all the necessary information to elaborate the matrix of evaluation of internal factors (EFI) whose result weighted is 2.58 points which indicates that the company must take advantage of the strengths in order to cancel the existing weaknesses. In the same way, the external analysis of the company was carried out according to the different political, economic, social, technological and environmental factors and the five Porter forces, with which the External Factor Evaluation Matrix (EFE) is determined. weighted is 2.53 points which indicates that the company has more opportunities than threats can cope. After completing the respective diagnosis, the strategies are developed through the high-impact matrix, thus obtaining the strategic objectives necessary for the company with its respective implementation budget: Carry out a promotions plan through gifts and discounts to achieve the loyalty of our customers (2,700.00); Establish a Mission, Vision, Values and Principles for a better organization of the company (270,90); Adapt the facilities with a waiting room for the convenience of the client through bank credits requested (11,000.00); Promote the services of the company through an advertising plan in the different media (2,140.00); Create a customer service department that allows us to leap over the competition and meet the needs of customers (1,900.00). To meet the established strategic objectives, a total annual budget of $ 18,010.90 is needed. Finally, the different conclusions and recommendations were made, which evidences the need to have a Strategic Plan for the good development of the company AEROCONEXOS CÍA. LTDA